2002
DOI: 10.1007/s00415-002-0763-8
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of linkage of nine neuronal nicotinic acetylcholine receptor subunit genes expressed in brain in autosomal dominant nocturnal frontal lobe epilepsy in four unrelated families

Abstract: Members of the ligand-gated neuronal nicotinic acetylcholine receptor (nAChR) gene family ( CHRNA4 and CHRNB2, coding for the alpha4 and beta2 subunits, respectively) are involved in autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE). However, ADNFLE is genetically heterogeneous and mutations in CHRNA4 and CHRNB2 account for only a minority of ADNFLE cases. Additional nAChR subunits expressed in the brain are candidates for this epilepsy. The involvement of all genes coding for brain-expressed nAChR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, as reported above, there are still a number of open questions concerning their role in the pathogenesis of the disease. Moreover, very recently we have shown that in four Italian families from our sample, none of the brain-expressed nAChR subunit genes so far identified and mapped on the human genome is associated with ADNFLE [11]. This finding points to the existence of at least a fourth locus for ADNFLE and/or to the involvement of new genes not belonging to the nAChR gene family or of yet unidentified brain-expressed nAChR genes in the pathogenesis of the disease.…”
Section: Open Questions On the Pathogenesis Of Adnflementioning
confidence: 71%
See 2 more Smart Citations
“…However, as reported above, there are still a number of open questions concerning their role in the pathogenesis of the disease. Moreover, very recently we have shown that in four Italian families from our sample, none of the brain-expressed nAChR subunit genes so far identified and mapped on the human genome is associated with ADNFLE [11]. This finding points to the existence of at least a fourth locus for ADNFLE and/or to the involvement of new genes not belonging to the nAChR gene family or of yet unidentified brain-expressed nAChR genes in the pathogenesis of the disease.…”
Section: Open Questions On the Pathogenesis Of Adnflementioning
confidence: 71%
“…The existence of three different loci for ADNFLE together with the recently reported suggestion of a fourth locus (different from nAChR subunit genes) [11], could be explained by considering ADNFLE as a monogenic disease in which a single mutation in one of the genes involved in the same neuronal network/s of nAChR is responsible for the phenotype. However, a different hypothesis could be put forward.…”
Section: Genetics Of Adnflementioning
confidence: 96%
See 1 more Smart Citation
“…30,31 CHRNA2 is a broadly-expressed subunit of nicotinic acetylcholine receptors. 32 In addition to its role in nicotine dependence and neurocognitive functioning, 33,34 CHRNA2 is located in a region of chromosome 8p that is suggested to contribute to psychiatric and neurodegenerative disorders. 35 Interestingly, nominal differential methylation of CHRNA2 was recently reported in monozygotic twins discordant for psychosis.…”
Section: Subject Enrollment Subjects Were Recruited From the Specialmentioning
confidence: 99%
“…A third locus for a yet unidentified gene exist on chromosome 15q24 . The presence of a fourth locus is likely since some families do not show linkage to any of the known loci (Bonati et al 2002;Derry et al 2008). Neuronal nicotic acetylcholine receptors are mostly presynaptic channels playing a role in the regulation of excitatory neurotransmitters.…”
Section: Temporal Lobe Epilepsy (Tle)mentioning
confidence: 99%